The impact of the top management teams' knowledge and experience on strategic decisions and performance. (31st August 2016) - Li, Peng-Yu
Abstract: This paper explores whether top management teams' (TMTs) knowledge and experience are significant predictors of a firm's strategic decisions and organization outcomes. The existing research throws little light on how firms with limited resources embedded in TMTs, particularly in emerging markets, innovate and achieve success in foreign countries. We focus on the impact of TMTs' functional background heterogeneity and international experience on innovation and internationalization, as well as examine the relationship between innovation, internationalization and performance. The proposed relationships are empirically investigated in a sample of Taiwanese-listed companies operating in the electronics industry. The results demonstrate a positive association between a TMT's functional background heterogeneity and a firm's innovation. Moreover, a TMT's international experience relates positively to a firm's innovation and internationalization, therefore firms with a higher level of innovation achieve a higher level of internationalization.